1992
DOI: 10.1103/physrevlett.69.973
|View full text |Cite
|
Sign up to set email alerts
|

Giant electropleochroism in GaAs-(Al,Ga)As heterostructures: The quantum-well Pockels effect

Abstract: We report on the biaxial response of photoluminescence to electric fields in GaAs quantum-well structures. For fields along [001], emission due to nominally forbidden excitons exhibits substantial differences between [110] and [1 TO] polarizations. Transitions which are allowed within the envelopefunction formalism show no noticeable anisotropy. In terms of symmetry, our observations relate to the linear electro-optic (Pockels) effect. The field dependence of the anisotropy is unusual in that it decreases wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 22 publications
1
45
0
Order By: Relevance
“…Kwok et al reported optical anisotropy of GaAs/Al x Ga 1Ϫx As multiple QW's under an electric field, which was known as the quantum-confined Pockels effect. 5,6 The unusual electric-field dependence of a forbidden transition could be well explained by the C 2v symmetry of interfaces. 8 The apparent effects of C 2v -interface symmetry on the optical anisotropy in In x Ga 1Ϫx As/GaAs QW's were evidenced by reflectance difference spectroscopy ͑RDS͒.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…Kwok et al reported optical anisotropy of GaAs/Al x Ga 1Ϫx As multiple QW's under an electric field, which was known as the quantum-confined Pockels effect. 5,6 The unusual electric-field dependence of a forbidden transition could be well explained by the C 2v symmetry of interfaces. 8 The apparent effects of C 2v -interface symmetry on the optical anisotropy in In x Ga 1Ϫx As/GaAs QW's were evidenced by reflectance difference spectroscopy ͑RDS͒.…”
Section: Introductionmentioning
confidence: 90%
“…[5][6][7][8] For an ͑001͒-oriented SQW with perfectly abrupt interfaces at zϭϮw/2, the hole-mixing induced by an electric field and the two interfaces can be included in the frame work of the classical envelope function theory by a perturbation Hamiltonian, …”
Section: Optical Anisotropy Induced By Electric Field "Quantum-comentioning
confidence: 99%
See 2 more Smart Citations
“…The HH-LH beats are by far more pronounced in the EOTC signal, which is dominated by the oscillatory contribution for resonant and OR excitation. The amplitude of the oscillations decreases by a factor of 4 for OR excitation, which is attributed to resonant contributions to the electro-optic effect in quantum wells [12], resonant anisotropic contributions to a coherent interband polarization [11], and the difference in the excitation density. The dephasing time of the beats decreases by less than a factor of 2 from resonant (t 700 fs) to OR excitation (t 360 fs).…”
Section: -9007͞96͞77mentioning
confidence: 99%